Evaluation of Gastroprotective Activity of Qarahine: A Polyherbal Formulation - Asad, Iqra; Anjum, Irfan; Alamgeer; Ahsan, Haseeb; Mushtaq, Muhammad Naveed (Indian Journal of Pharmaceutical Education and Research, 2021)
Background and Aim: Qarahine, a polyherbal formulation consisting of natural active ingredients, is used to treat peptic ulcer. The aim of the present study was to investigate the protective effect of qarahine against aspirin (200 mg/kg) and ethanol (5 ml/kg) induced gastric ulcer rat models. Methodology: The pH of stomach contents, numbers of lesions in gastric mucosa, severity score, ulcer index and percentage protection were determined. The stomachs mucosa was also evaluated for morphological changes. Three doses of qarahine (250, 500 and 1000 mg/kg) were evaluated. Omeprazole (20 mg/kg) was used as a standard drug. Results: Different doses of qarahine significantly raised pH and reduced the ulcer index in both aspirin and ethanol induced ulcerative rats. Qarahine (500 mg/kg) provided 29.9% and 32.9% protection in aspirin and ethanol-induced ulcer models. Histopathological studies validated the biochemical outcomes. Conclusion: This study suggested gastroprotective effect of qarahine which might be due to increase in gastric mucus secretions and mucus protective mechanisms. However, further studies are necessary to clarify the mechanisms of action of qarahine.
Keywords: Qarahine; Gastroprotective; Aspirin; Ethanol; Ulcer index